The impact of engaging with clients’ trauma stories: Personal and organizational strategies to manage probation practitioners’ risk of developing vicarious traumatization - Lee, Rosie (Probation journal, 2017)
This article considers the impact on probation practitioners of exposure to, and engagement with, clients’ trauma stories. Drawing on research in related client-focused fields, the article discusses the constructivist self-development theory of vicarious traumatization and how the probation practitioner role places practitioners at risk of experiencing negative changes to their emotional well-being. Development of vicarious traumatization is discussed with reference to changes in organizational structure brought about through the Transforming Rehabilitation (TR) agenda. It is argued practitioners’ use of self-care practices, the need for effective practitioner-supervisor support systems and appropriate and trauma-focused training would all help to reduce the risk of practitioners developing vicarious traumatization.